Global Britain in the grey zone: Between stagecraft and statecraft. Issue 4 (2nd October 2021) - Rauta, Vladimir; Monaghan, Sean
ABSTRACT: The United Kingdom's integrated defense and security review put "grey zone" or "hybrid" challenges at the center of national security and defense strategy. The United Kingdom is not alone: The security and defense policies of NATO, the European Union, and several other countries (including the United States, France, Germany, and Australia) have taken a hybrid-turn in recent years. This article attempts to move the hybrid debate toward more fertile ground for international policymakers and scholars by advocating a simple distinction between threats and warfare. The United Kingdom's attempts to grapple with its own hybrid policy offer a national case study in closing the gap between rhetoric and practice, or stagecraft and statecraft, before an avenue of moving forward is proposed—informally, through a series of questions, puzzles, and lessons from the British experience—to help international policy and research communities align their efforts to address their own stagecraft-statecraft dichotomies.